Analysis of the structural behavior and strength of cold-formed steel Z90 profiles with the use of ribs - Soares, Jose Pedro Leal; Mendes, Luiz Carlos (Seven Editora, 2023)
The knowledge about the types of materials and profiles in structural projects has become increasingly important with the advance of technology in structural areas. The evolution of the cross-section geometry of a profile is of paramount importance to generate great efficiency in the structural area along with other benefits such as low production costs. In this research, the results of a study on the stability behavior of cold-formed steel bars with Z90 cross-section chosen through NBR 6355:2012 are presented and discussed. The applicability or not of V-shaped ribs in the web and/or in the flanges of the profiles is considered, which occur compression load at their ends and being studied for each example a simply supported member. The research aims to analyze the structural behavior of the profiles, identifying the different behaviors for each type of cross-section studied with the deformation modes that occur and to reach a conclusion as to the use of ribs being an important factor for increasing the resistance of the bar. Analysis of structural stability was performed identifying geometries affected by instability phenomena with the help of the GBTUL program, which uses the Generalized Beam Theory generating the results of bifurcation loads and modal participation diagrams that are of great importance to verify the structural behavior of the studied profiles. With the results generated, the profile with the introduction of ribs both on the web and on the flanges had higher resistance, followed by the profile with ribs only on the web, in third place the profile with ribs only on the flanges and with the lowest resistance, the profile without ribs. Thus, it can be concluded that the introduction of ribs generated a greater resistance of the profile regarding the compression load applied at its extremities. DOI:https://doi.org/10.56238/alookdevelopv1-012